Titanium Carbide (Ti3C2Tx) MXene Ornamented with Palladium Nanoparticles for Electrochemical CO Oxidation - Belal Salah (14150460) (2023)
Titanium carbide (Ti3C2Tx) MXene possesses various unique physicochemical and catalytic properties. However, the electrochemical CO oxidation performance is not yet addressed experimentally. Herein, Ti3C2Tx (TX=OH, O, and F) ordered and exfoliated two-dimensional nanosheets ornamented with semi-spherical palladium nanoparticles (2.5 Wt. %) with an average diameter of (10±1 nm) (denoted as Pd/Ti3C2Tx) is rationally designed for the electrochemical CO oxidation. The fabrication process is based on the selective chemical etching of Ti3AlC2 and delamination under sonication to form Ti3C2Tx nanosheets that are used as a substrate and reducing agent for supporting in situ growth of Pd nanoparticles via impregnation with Pd salt. Interestingly, Pd-free Ti3C2Tx displayed inferior CO oxidation activity, while Pd/Ti3C2Tx enhanced the CO oxidation activity substantially. This is attributed to the combination of outstanding physicochemical properties of Ti3C2Tx and the catalytic merits of Pd nanoparticles. Other Information Published in: Electroanalysis License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: http://dx.doi.org/10.1002/elan.202100269